Integrating isotopic, microbial, and modeling approaches to understand methane dynamics in a frequently disturbed deep reservoir in Taiwan. Issue 6 (18th September 2017) - Itoh, Masayuki; Kojima, Hisaya; Ho, Pei‐Chi; Chang, Chun‐Wei; Chen, Tzong‐Yueh; Hsiao, Silver Sung‐Yun; Kobayashi, Yuki; Fujibayashi, Megumu; Kao, Shuh‐Ji; Hsieh, Chih‐hao; Fukui, Manabu; Okuda, Noboru; et al.
Abstract: It has been estimated that more than 48% of global methane emissions from lakes and reservoirs occur at low latitudes (<24°). To improve this estimate, knowledge regarding underexplored ecosystems, particularly deep lakes and reservoirs in Asian monsoon regions, is needed because the magnitude of methane emissions is influenced by lake bathymetry and climatic conditions. We conducted long‐term studies beginning in 2004 at Feitsui Reservoir (FTR) in Taiwan, a subtropical monomictic system with a maximum depth of 120 m to monitor seasonal and interannual variations of three key characteristics and to understand the mechanisms underlying these variations. Key characteristics investigated were as follows: (1) the balance of primary production and heterotrophic respiration as a determinant of vertical oxygen distribution, (2) methane production at the bottom of the reservoir, oxidation in the water column, and emissions from the lake surface, and (3) the contribution of methane‐originated carbon to the pelagic food web through methane‐oxidizing bacteria (MOB). This review highlights major achievements from FTR studies integrating isotopic, microbial, and modeling approaches. Based on our findings, we proposed two conceptual models: (1) a model of methane dynamics, which addresses the differences in methane emission mechanisms between deep and shallow lakes, and (2) a spatially explicit model linking benthic methane production to the pelagic food web, which addresses the diversity of MOB metabolisms and their dependence on oxygen availability. Finally, we address why long‐term studies of subtropical lakes and reservoirs are important for better understanding the effects of climate on low‐ to mid‐latitude ecosystems.